Insulin receptor activation effects on synaptosomal 2-AG hydrolysis in an amyloidosis model induced by AB oligomers - Pascual, Ana Clara (2019)
Insulin (Ins) plays an important role in synaptic plasticity and is tightly related to Alzheimer´s disease (AD). Aβ oligomers (AβO), which are responsible for synaptic dysfunction in AD, can bind to Ins receptor (IR) and can therefore be internalized into neurons. AβO also disrupt the synaptic membrane and diminish 2-AG availability, the main neuroprotective cannabinoid. Ins can prevent AβO binding to IR, thus attenuating its neurotoxicity. Here, we hypothesized that Ins prevent AβO deleterious effects on 2-AG metabolism. To this end, we isolated cerebral cortex synaptosomes (syn) by differential centrifugation purified in ficoll gradients and preincubated them with 10 µM LY294002 (phosphatidylinositol-3-kinase -PI3K- inhibitor) or 100 µM genistein (tyrosine kinase inhibitor) for 10 min, and subsequently incubated with 0.2 mM vanadate (protein-tyrosine phosphatase inhibitor), 100 nM Ins, or 0.2 mM vanadate plus 100 nM Ins, for 30 min. Syn were then incubated for 10 min with or without 0.1 µM AβO. After this incubation, activation of IR signaling by Western Blot, released LDH activity, and 2-AG hydrolysis activity were evaluated. It was observed that a 30 min incubation with Ins and vanadate activated IR and Akt (p<0.05). The subsequent incubation with AβO did not alter IR activation (p>0.05). As to syn membrane damage, neither of the pretreatments could prevent AβO effect on LDH release (p>0.05). On the other hand, Ins and vanadate decreased 2-AG hydrolysis (p<0.01) and their effect was not observed if syn were preincubated with LY (p>0.05). However, in the presence of AβO, Ins and vanadate failed to alter 2-AG hydrolysis (p>0.05) and LY increased this activity (p<0.001). Our results show a regulation of 2-AG hydrolysis by Ins, possibly increasing its availability via IR and involving PI3K pathway, which is abolished by AβO. The effect of AβO appears to be independent of IR and to involve PI3K activity. Ins also failed in preventing AβO damage in synaptic membrane.